Cuius regio? Ideological and Territorial Cohesion of the Historical Region of Silesia (c. 1000-2000) vol. 2. The Strengthening of Silesian Regionalism (1526–1740) - Harc, Lucyna; Wąs, Gabriela; Maroń, Jerzy (Publishing House eBooki.com.pl, 2014)
This book is the second in a series dedicated to the cohesion of Silesia as a region. Published studies focuse on the processes that were carried out in years 1526–1740. This study has been conducted under the auspices of the European Science Foundation as part of the programme entitled Cuius regio: An analysis of the cohesive and disruptive forces determining the attachment and commitment of (groups of) persons to and the cohesion within regions. An analysis of the phenomena which occurred in the administrative, economic, social, ethnic and cultural spheres, as well as in respect of the self-identification and identity of inhabitants has demonstrated what a complex region Silesia was under the rule of Habsburg dynasty. Administratively, it was highly fragmented, it possessed an expansive network of government offices, and was economically, ethnically, linguistically and religiously diverse. The beginning of the 17th century constituted a significant turning point. The eruption of the Thirty Years’ War led to deep social transformations, altered the religious situation, and generated serious economic consequences. The first half of the 17th century also bore fruit in the form of new cultural and artistic phenomena. The conclusion derived from published studies indicates that the cohesive tendencies were prevalent – when compared to the situation before 1526 – however, disruptive tendencies existed as well, especially concerning religion-based conflicts.
Keywords: regional history; identity; integration; disintegration; social groups; art; ethnicity; administration; economy; social cohesion; Silesia